Legal access to traditional knowledge associated with biodiversity in Brazil: New national perspectives (Research, Society and Development, 2021)
Since the 1980s, there is an increase in the availability of technological applications of genetic resources from biodiversity based on Associated Traditional Knowledge (ATK). That happens to try to find solutions to the problems faced by humanity.  Since the beginning of the 1990s, ATK has been subject to a discussion about its legal use.  Different international guidelines and national juridical instruments have emerged to establish appropriate conditions for lawful access, economic exploitation, and fair sharing of benefits. The establishment of such conditions has become relevant for the design of development strategies of megadiverse countries. The discussions also go through the importance of preserving biodiversity, sustainable exploitation, cultural impacts, and undue appropriations. Our objective was to analyze official indicators of legitimate access to ATK to explain national expectations about how its public policies are effective. The present study is characterized by being an exploratory, documentary, quantitative, historical and longitudinal research. Official documents and data published by the body responsible for the regulation and deliberation of legal access to CTA in Brazil during the period from 2002 to 2020 were analyzed. The results demonstrate a significant growth in the number of records of scientific and technological activities with access to CTA regularized in the period. Brazil, which was driven by the implementation of SisGen. However, on the other hand, the transparency of information is impaired due to the unavailability of information that was disclosed by CGEN during the term of MP 2,186 / 2001.